The Calculations of Wiener μ-invariant and someTopological Indices on the Corona Graph - Rasool, Kavi; Rasheed, Payman A. (Iraqi Journal of Science, 2023)
A topological index, commonly referred to as a connectivity index, is a molecular structural descriptor that describes a chemical compound's topology. Topological indices are a major topic in graph theory. In this paper, we first define a new graph, which is a concept from the coronavirus, called a corona graph, and then we give some theoretical results for the Wiener and the hyper Wiener index of a graph, according to ( the number of pairs of vertices (u, v) of G that are at a distance . Moreover, calculate some topological indices degree-based, such as the first and second Zagreb index, , and index, and first and second Gourava index for the recent graph. In addition, we introduced a new topological index, the , which was inspired by the definition of the index.